Legal Status of the Limited Liability Partnership by the Legislation of the Republic of Kazakhstan - Yestemirov, M.A. (World Applied Sciences Journal Vol 24, No 11, 1420-1423, 2013)
Along with the individual, the legal entity is one of the active participants of economic relations. Properties of the legal entity give founders such opportunities as collection of capitals, decrease of enterprise risk and realization of big projects, which is undoable for individuals. Founders of these legal entities not only benefit financially, but also realize many socially useful projects. Therefore, proper legal regulation of legal entities’s activity is important for an economic turn. This article analyzes the legislations that regulate activity of the limited liability partnership in the Republic of Kazakhstan. In particular, it concentrates on the structure of founders of LLP, an order of alienation of a share in charter fund and possibility of transfer of the LLP to trust management.
Keywords: Limited liability partnership, Charter fund, Founder, Gaps in the legislation